How responsive is body weight to transitory income changes? Evidence from rural Tanzania - Niklas Bengtsson (Uppsala University, Department of Economics, 2007)
We use time-series of rainfall along with individual fixed effects to estimate the response of body weight to transitory changes in house-hold income and expenditure. Our data consist of a longitudinal sample of subsistence farmers in rural Tazania, representing one of the poorest populations in the world. We find that the response of body weight to transitory changes in household income is positive on average, but that the impact decreases with age and being male. For female children, a ten percent increase in household income implies an increase in body weight with about 0.4 kilo. The body weight of male adults is practically invariant to income changes.
Keywords: D13; I12; O12; 330; Income variability; Consumption; Nutrition; sub-Saharan Africa; Haushaltseinkommen; Familie; Ernährungsverhalten; Zeitreihenanalyse; Tansania